(3GdHjGf aj abg GdTGaYjIs - (3jMji Hf SGde Hf CSYO Hf jMji, CHh GdMSjf GdYeQGfj,J (B558 (3g` s ((3eMeO Hf OGhO NVQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChLOfG HbOQJg , hCQTOfG HNdbg Edi eYQaJg CeG HYO , adeG cGf ePgH GdTGaYi EYJbGOi s
(3BNQgG (B:s
(3jfJgi HEfJgGA HGH GddHGS bhdg (B: (3hdjS cPdc SGFQ GdMjhGfGJ aEfg jLhR GdEfJaGY Hg ai MGd GdMjGI hHGddg GdJhajb s
(3fSNI NRGFfjIs
(3HBNQgG SeGY eDQN SfI (B810 (3g`s
(3hcJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs